Aspectos ambientales y culturales de los nodos panbiogeográficos prioritarios para mamíferos terrestres del centro-sur de México - Corona-Mendoza, Willie; Escalante, Tania (Instituto de Ecología, A.C., 2021)
The Panbiogeographical Nodes (PN) are relevant contributions of the evolutionary biogeography to the biodiversity conservation, which are interpreted as the spatial-temporal overlapping of different ancestral geobiotic fragments, allowing identify priorities to preserve both species and evolutionary origins richness. On the other hand, mammals are a group with an important cultural connotation in the indigenous regions of Mexico, where they are used mainly as food and medicine. Because Mexico is one of the countries with a close correlation between its great biological and cultural diversities, the aim of this research focused on the prioritization and environmental and cultural characterization of PN for the conservation of mammals in central-southern Mexico. The prioritization of species richness was carried out employing three criteria, and the Prioritized PN (PPN) were environmental and culturally characterized. From the seven groups of PN integrated by 31 PN and 3 PN without group, we prioritized 23 NP. The most of the PPN were located in the Chiapas Highlands biogeographic province, followed by the Sierra Madre del Sur, while the Transmexican Volcanic belt had the lower number of PPN. In the first provinces, there were overlapping and agglomeration of PPN, mainly in the Altos de Chiapas and the Sierra Juárez. These last sites seem to be the geographical areas more complex from biogeographic-evolutionary, physical-geographic, and cultural viewpoints. For conservation, the preservation of these PPN will allow to protect many natural and cultural resources.